Venoarterial Extracorporeal Membrane Oxygenation for Severe Neonatal Acute Respiratory Distress Syndrome in a Developing Country - Hong, Xiaoyang; Zhao, Zhe; Liu, Zhenqiu; Liu, Change; Wang, Jie; Quan, Xueli; Wu, Hui; Ji, Qiong; Sun, Jianwei; Cheng, Donglinag; Feng, Zhichun; Shi, Yuan (Frontiers in Pediatrics, 2020)
Objective Extracorporeal membrane oxygenation (ECMO) has supported gas exchange in neonates with severe respiratory failure for over 40 years. The definition and diagnosis of neonatal acute respiratory distress syndrome (ARDS) was made according to the criteria firstly established by a Montreux Conference in 2017. By far, there has been no ECMO efficiency studies in neonatal ARDS. We aimed to compare the outcomes of neonates with severe ARDS supported with and without ECMO. Design Retrospective pair-matched study. Setting In the present retrospective pair-matched study, the outcomes of severe ARDS with ECMO support and without ECMO support were analyzed and compared. Propensity score matching was conducted. The study subjects were selected from China Neonatal ECMO (CNECMO) study. In total, five hospitals were included in the CNECMO study. Detailed demographic and clinical data were recorded to match patients. The primary endpoint was in-hospital mortality. Secondary outcomes included ventilator-time, ICU stay, hospitalization costs and cranial MRI results. Patients 145 neonates with severe ARDS (Oxygenation Index, OI≥16) from 5 hospitals. Interventions Our results demonstrate that in neonates with severe ARDS, ECMO-support have superior outcomes compared with non–ECMO-support. A randomized controlled clinical trial of ECMO in severe neonatal ARDS should be performed to provide definitive answers. Measurements and Main Results We collected the data of 145 neonates with severe ARDS(Oxygenation Index, OI≥16) from 5 hospitals. Among them, 42 neonates received venoarterial (VA) ECMO support, and the remained 103 neonates were treated with conventional mechanical ventilation. The mortality of ECMO-supported neonates was not significantly different compared with the ESLO neonatal respiratory-supported from 2012 to 2018(23.8% vs 32.5%, p=0.230). After propensity score matching (31 matched pairs), the ECMO-supported in-hospital mortality was 6 of 31 (19.4%), and the non–ECMO-supported was 18 of 31 (58.1%) (p=0.002). Hospitalization costs of survivors in ECMO-supported neonates were significantly higher than that of non-ECMO-supported neonates(p<0.001). There was no difference of ventilator-times (p=0.206), ICU stay(p=0.879) and cranial MRI(p=0.899) between the survivors of ECMO-supported and non–ECMO-supported neonates. Conclusions By far, there has been no ECMO efficiency studies in neonatal ARDS. This study found that ECMO-support have superior outcomes compared with non–ECMO-support in neonates with severe ARDS.